2020
DOI: 10.13189/cea.2020.080424
|View full text |Cite
|
Sign up to set email alerts
|

Design Initiative Implementation Framework: A Model Integrating Kolmogorov-Smirnov in Sustainable Practices for Triple-Bottom-Line Principles in Construction Industry

Abstract: TAGLINE: Eliminate Waste, Build Quality, Empower Team. Every construction project is characterized by being complex. Over the years, the efficiency and performance of the construction industry in the Philippines have been declining. Plus, the reality is that construction has been one of the largest polluters ever-since it started. This study proposes a plan of action that addresses these situations by introducing the concept of lean construction principles and value management. The purpose of this study is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…It conforms to Silva et al findings that stable and robust culture is defined by identifying and relating to exceptional individuals and teams who adhere to the organization's values. Furthermore, they identified that developing the people and promoting teamwork improves the organization's values [20] The research indicates that the construction industry's historical adversarial approach has inhibited the formation of trusting relationships. The company in the case study has a long history in the construction industry.…”
Section: Case Study 1 Discussion -Impact On the Companymentioning
confidence: 99%
“…It conforms to Silva et al findings that stable and robust culture is defined by identifying and relating to exceptional individuals and teams who adhere to the organization's values. Furthermore, they identified that developing the people and promoting teamwork improves the organization's values [20] The research indicates that the construction industry's historical adversarial approach has inhibited the formation of trusting relationships. The company in the case study has a long history in the construction industry.…”
Section: Case Study 1 Discussion -Impact On the Companymentioning
confidence: 99%
“…( 1 ) ( 2 ) where "I" is the quantity of input parameters, "H" is the quantity of hidden neurons and "O" is the quantity of output parameters. Using this equation, this study arrived with the 81 respondents required for the training of the network.…”
Section: Data Collectionmentioning
confidence: 99%
“…One of the most difficult undertakings in a construction project is the selection of the most suitable individual for the job. Currently, project managers in the construction industry requires versatility and adaptability to multiple functions and roles wherein a key element is their knowledge and skills gained from years of experience and training [1,2]. The management competency is classified into four areas: self -awareness, systems thinking, action management and solution focus as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Construction is becoming less effective and efficient [3]. Limited collaboration on and off the site has been one of the industry's major issues because most construction projects rely on strong productivity to deliver on schedule, and this depends on how well stakeholders can work together and communicate [4].…”
Section: Introductionmentioning
confidence: 99%